2008
DOI: 10.1111/j.1530-0277.2008.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Epigenetics in the Actions of Alcohol

Abstract: This review deals with the recent developments on the epigenetic effects of ethanol. A large body of data have come from studies in liver and in neuronal systems and involve post-translational modifications in histones and methylations in DNA. Ethanol causes site selective acetylation, methylation, and phosphorylation in histone. With respect to methylations the methyl group donating system involving S-adenosyl methionine appears to play a central role. There is contrasting effect of acetylation versus methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(146 citation statements)
references
References 93 publications
1
144
0
1
Order By: Relevance
“…In the case of the chronic ethanol-induced decrease in DNA and histone methylation, it is likely that these changes can be prevented by SAMe treatment [4]. Likewise, LPS toxicity increases binding of trimethylated H3K4 to the iNOS and TNFa promoter, and this is blocked by SAMe treatment by inhibiting the trimethylated H3K4 binding to their promoter response element.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the chronic ethanol-induced decrease in DNA and histone methylation, it is likely that these changes can be prevented by SAMe treatment [4]. Likewise, LPS toxicity increases binding of trimethylated H3K4 to the iNOS and TNFa promoter, and this is blocked by SAMe treatment by inhibiting the trimethylated H3K4 binding to their promoter response element.…”
Section: Discussionmentioning
confidence: 99%
“…Deacetylation of histones leads to inactivation of gene expression. The role of epigenetic reprogramming of gene expression in the liver in response to ethanol feeding has recently been reviewed [4].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic ethanol exposure causes an alteration in liver cell memory by changing the epigenetic mechanisms, thus causing significant liver pathology that persists after ethanol withdrawal [30] . Dr. French's group has shown that cells forming MDBs have a memory of the exposure to the drug even four months after drug withdrawal [31] .…”
Section: Epigenetic Mechanisms and Proteasome Inhibitionmentioning
confidence: 99%
“…More epigenetic mechanisms still need to be elucidated with respect to alcoholism, particularly histone modifications, such as methylation, phosphorylation and ubiquitinylation of lysine and arginine residues. The task will be to identify the modifications and the specific modifying enzymes that regulate gene expression and account for the cellular memory observed when ethanol is fed chronically [30] . For example, it has been reported that a global increase in histone H3 lysine 9 acetylation, histone H3 lysine 4 dimethylation and H3 lysine 27 trimethylation is found in the liver of rats fed ethanol chronically [48] , which correlates with an increase and a decrease, respectively, in transcriptionally active promoters.…”
Section: Modifying Enzymesmentioning
confidence: 99%
“…Pregnancy is a particularly sensitive period, and in utero exposure to alcohol has teratogenic effects on the fetus, partially linked to epigenetic mechanisms (Shukla et al, 2008;Guerri et al, 2009). In mice, exposing A vy dams to ethanol increases methylation at the A vy allele, silences agouti expression, and thereby shifts the offspring phenotype toward agouti colored coat (Kaminen-Ahola et al, 2010).…”
Section: Drugsmentioning
confidence: 99%